2006
DOI: 10.1097/01.shk.0000228170.94468.e1
|View full text |Cite
|
Sign up to set email alerts
|

Children Under 4 Years Are at Greater Risk of Mortality Following Acute Burn Injury

Abstract: It is important to have an accurate understanding of mortality risk in children to make sound treatment decisions and to advise parents and families. Several studies have found that children younger than 4 years are at greater risk for mortality from burn injury than older children, although other studies have found no difference. All of these studies, however, have been limited by small sample sizes from single burn centers. The objective of this study was to assess age-related mortality risk in a sample of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 20 publications
8
22
2
2
Order By: Relevance
“…The most common reasons for mortality were acute kidney failure, sepsis, shock and disseminated intravascular coagulation. [2,[4][5][6][7][8][9][11][12][13][15][16][17][18] While the mean mortality rate for all burns was 1.31% in our study, it was 0.64% for scalding burns, 2.35% for flame burns, 5.88% for electrical burns and 25% for flame-inhalation burns. The rate was 18.18% for burns of 40% and above surface area.…”
Section: Discussionmentioning
confidence: 93%
“…The most common reasons for mortality were acute kidney failure, sepsis, shock and disseminated intravascular coagulation. [2,[4][5][6][7][8][9][11][12][13][15][16][17][18] While the mean mortality rate for all burns was 1.31% in our study, it was 0.64% for scalding burns, 2.35% for flame burns, 5.88% for electrical burns and 25% for flame-inhalation burns. The rate was 18.18% for burns of 40% and above surface area.…”
Section: Discussionmentioning
confidence: 93%
“…[3][4][5][6][7] In our study, the mean age at the time of scalding was 3.2 years and scalding accounted for 85.6% of our pediatric inpatient group. The main source of scalding is hot liquid, especially the hot water used for making tea, a traditional practice in our country.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed similarly in developed countries. [6,8,9] Flame burn was the second most common cause of burn injuries. Childhood flame burns usually occurred outdoors, often as a result of the ignition of flammable liquids.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there is strong evidence that, when comparing children based on burn injuries of similar size and aetiology, children aged <4 years are at substantial risk for death compared with their older counterparts. [10] We compared our overall mortality rate with rates for various institutions around the world (Table 5).…”
Section: Discussionmentioning
confidence: 99%